Targeted bio-distribution of drugs to the lymphatic system - Jewell, Adelaide (2022)
Targeted drug delivery to the intestinal lymphatic system has emerged as an important goal in drug development for the treatment of a number of clinical indications. These include, cancers, inflammatory disorders and infectious diseases. Following oral administration, small molecule drugs with specific physiochemical properties, have been shown to associate with lipoproteins called chylomicrons in the enterocytes of the small intestine. Chylomicron associated drugs then bypass hepatic uptake and enter the mesenteric lymph nodes (MLN). Oral coadministration of highly lipophilic small molecule drugs with lipids had subsequently been identified as an effective mechanism for delivering highly lipophilic small molecule drugs to the MLN in high concentrations. One example is Cannabidiol (CBD), which was shown to undergo lymphatic transport following oral administration with lipids and has received significant research interest for the treatment of inflammatory disorders.